2022
DOI: 10.3389/fpls.2022.923717
|View full text |Cite
|
Sign up to set email alerts
|

Features of Activity of the Phenylpropanoid Biosynthesis Pathway in Melanin-Accumulating Barley Grains

Abstract: Barley (Hordeum vulgare L.) grain pigmentation is caused by two types of phenolic compounds: anthocyanins (which are flavonoids) give a blue or purple color, and melanins (which are products of enzymatic oxidation and polymerization of phenolic compounds) give a black or brown color. Genes Ant1 and Ant2 determine the synthesis of purple anthocyanins in the grain pericarp, whereas melanins are formed under the control of the Blp1 gene in hulls and pericarp tissues. Unlike anthocyanin synthesis, melanin synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Out of the 11 candidate genes mapped in Hor13821, only HvBlp was highly and specifically expressed in the black-coloured husk/pericarp tissues in BNIL at S3 stage: BS3, while the other 10 genes either were barely expressed or displayed no significant difference between BINL and YNIL (Figure 1d; Table S2). In addition, we analysed another published transcriptome datasets of different black-and yellow-coloured barley lines (Table S2; Glagoleva et al, 2022) and confirmed that HvBlp was uniquely transcribed in the black barley genotype. Next, we performed qRT-PCR on HvBlp in 100 black and 100 yellow inbred lines.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…Out of the 11 candidate genes mapped in Hor13821, only HvBlp was highly and specifically expressed in the black-coloured husk/pericarp tissues in BNIL at S3 stage: BS3, while the other 10 genes either were barely expressed or displayed no significant difference between BINL and YNIL (Figure 1d; Table S2). In addition, we analysed another published transcriptome datasets of different black-and yellow-coloured barley lines (Table S2; Glagoleva et al, 2022) and confirmed that HvBlp was uniquely transcribed in the black barley genotype. Next, we performed qRT-PCR on HvBlp in 100 black and 100 yellow inbred lines.…”
Section: Resultssupporting
confidence: 55%
“…(a) The transcriptional expression of Blp1 and Blp2 homologous genes in the spikes of barley NILs BLP (black lemma and pericarp), PLP (purple lemma and pericarp), BP (black and purple) and of cv. Bowman (BW) at the booting stage (1), late milk stage (2), and early dough stage (3) (Glagoleva et al ., 2022 ). (b) The transcriptional expression of Blp1 and Blp2 homologous genes in the husk/pericarp tissues of BNIL and YNIL at green (early milk stage, S1) and black grain stages (late milk, S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dark-colored barley seeds have higher contents of phenolic compounds and lignin than uncolored ones. It was suggested that melanin biosynthesis genes may be connected to phenylpropanoid-derived biosynthesis pathways [9].…”
Section: Introductionmentioning
confidence: 99%